PELATIHAN PEMANFAATAN ARTIFICIAL INTELLIGENCE UNTUK PEMASARAN DIGITAL PADA KOPERASI PEMBERDAYAAN UMMAT DAARUT TAUHID TANGERANG SELATAN - Aan Purnama; Kiki Dwi Wijayanti; Ade Yusuf (Abdi Jurnal Publikasi, 2025)
This Community Service activity aims to enhance the understanding and skills of the management and members of KOPMU-DT in utilizing Artificial Intelligence (AI) technology for digital marketing. Through an interactive training program, participants were introduced to the basic concepts of AI, practical applications in marketing, and the use of tools such as ChatGPT, Canva AI, Google Analytics, and Meta Ads. The implementation method consisted of five main stages: (1) conducting observations and needs assessments through interviews and preliminary surveys; (2) developing training modules based on identified needs; (3) delivering a two-day workshop using interactive lectures, case studies, hands-on simulations with AI tools, and group discussions; (4) post-training mentoring sessions to assist participants in formulating AI-based digital marketing strategies; and (5) evaluating the program through pre-tests, post-tests, and participant satisfaction surveys. The results indicated a significant improvement in participant comprehension based on the pre-test and post-test scores. Over 85% of participants demonstrated increased knowledge and understanding of AI applications in digital marketing. Furthermore, participants were able to develop at least two AI-based digital marketing campaigns and gained an introductory understanding of CRM and chatbot implementation as part of the cooperative's digital strategy. The outcomes of this program include: (1) a training module on “Utilizing AI for Digital Marketing,” (2) two AI-based digital marketing campaigns developed by participants, (3) an evaluation report based on pre-test and post-test results, (4) measurable improvement in cooperative HR capacity through impact surveys, and (5) documentation of the program, including attendance lists, photos, and participant testimonials.